Edukasi Etika Bisnis : Pengelolaan Usaha pada UMKM di Desa Rato Kecamatan Bolo - Muhammad Firdaus; Kartin Apriani; Wulan Rizki Ramdani; Desi Fitrianingsih (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Fostered partners are partners formed by KKN group III students in Rato Village, Bolo Subdistrict while business actors are those in the village of Rato with the type of business, namely typical regional snacks. This activity aims to provide knowledge to fostered partners and also business people in Rato Village about business ethics that partners need to have in doing business. The method offered to partners / SMEs is in the form of education / socialization using LEAFLETS which are carried out door to door. The material provided in the leaflet includes a discussion of (1) the role of ethics in doing business for MSME actors, (2) the benefits of doing business for MSME actors, (3) the application of ethical principles in doing business in financial, marketing, production and HR activities. The results of this activity show that flower pangaha MSMEs are very enthusiastic in listening and discussing during the activity. In addition, it can provide knowledge about ethics in running a business.